2002
DOI: 10.1002/ccd.10162
|View full text |Cite
|
Sign up to set email alerts
|

Stent supported angioplasty for coronary arterial stenosis following the arterial switch operation

Abstract: We present a case of a patient who underwent stent-supported angioplasty for left main bifurcation disease following the arterial switch operation. Prior to this procedure, the patient underwent surgical repair of the left coronary ostium and subsequently coronary artery bypass surgery with an arterial graft to the left anterior descending artery. We could not find a similar report in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…1 Indeed, patients with coronary stenosis are treated using percutaneous coronary intervention. 1,2 Specifically, El-Segaier et al 1 reported 3 cases of left main coronary artery (LM) stenosis treated using stenting, and Abhaichand et al 2 described a case of stentsupported angioplasty after surgical repair of the left coronary ostium and CABG. We report the case of an 8-year-old girl with chronic total occlusion (CTO) of the LM after ASO, successfully treated using percutaneous coronary intervention.…”
Section: R Esum Ementioning
confidence: 99%
“…1 Indeed, patients with coronary stenosis are treated using percutaneous coronary intervention. 1,2 Specifically, El-Segaier et al 1 reported 3 cases of left main coronary artery (LM) stenosis treated using stenting, and Abhaichand et al 2 described a case of stentsupported angioplasty after surgical repair of the left coronary ostium and CABG. We report the case of an 8-year-old girl with chronic total occlusion (CTO) of the LM after ASO, successfully treated using percutaneous coronary intervention.…”
Section: R Esum Ementioning
confidence: 99%
“…The alternative is surgery for coronary arterial bypass or patch augmentation of the orifices. [839][840][841][842][843][844][845] Experience in these invasive treatments remains limited, and conclusions on the outcome in the longer term are yet to be made.…”
Section: B) Medical Follow-upmentioning
confidence: 99%
“…8.4.5.2 Percutaneous transluminal coronary angioplasty in infants and young children. This procedure includes the possibility of inserting a coronary stent, as a firsttime intervention to alleviate coronary stenosis, or after a previous coronary patch angioplasty operation [382,[396][397][398]. In these rare patients a policy of routine angiographic evaluation of the coronary arteries within the first 2-3 years after repair is advisable [382].…”
Section: Reoperations For Coronary Lesionsmentioning
confidence: 99%